2004
DOI: 10.2176/nmc.44.311
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Recurrence of Granulocytic Sarcoma Manifesting as Extra- and Intracranial Masses

Abstract: A 30-year-old female presented with a rare case of isolated recurrence of granulocytic sarcoma manifesting as extra-and intracranial masses 16 months after successful treatment of acute myeloblastic leukemia (M-2). She presented with a swelling located on her forehead that had appeared just after hitting her forehead, and never diminished in size. The mass was elastic hard and not freely mobile. Computed tomography and magnetic resonance imaging demonstrated enhanced masses in the right frontal extra-and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…On the other hand, surgery could increase the risk of infection and central nervous system dissemination, so there is no advantage over chemotherapy and irradiation. 13) The present two cases demonstrate that neurosurgeons should pay attention to the occurrence of isolated recurrence of intracranial or extra-and intracranial GS, especially in patients with a history of hematologic neoplasms.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, surgery could increase the risk of infection and central nervous system dissemination, so there is no advantage over chemotherapy and irradiation. 13) The present two cases demonstrate that neurosurgeons should pay attention to the occurrence of isolated recurrence of intracranial or extra-and intracranial GS, especially in patients with a history of hematologic neoplasms.…”
Section: Discussionmentioning
confidence: 67%
“…A 30-year-old female presented with isolated recurrence of GS manifesting as extra-and intracranial masses 16 months after complete remission of M2. 13) A 34-year-old female with AML-M3 in remission developed unilateral hearing loss caused by cerebellopontine angle GS identified by MR imaging 27 months after remission, but histological examination of the GS specimen revealed AML-M4. 8) A 45-year-old male patient diagnosed with AML-M4 who remained in complete remission for 16 years, then a large subdural GS was found, and the final histological examination showed AML-M0.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytic sarcoma, also termed "chloroma" for the green color, is an extramedullary solid tumor composed of immature myeloid cells or myeloblasts and it can occur in leukemia, myeloproliferative and myelodysplastic disorders (3). It can occur anywhere in the body and at any age, involving bone, periostium, lymph nodes, skin, breast, ovary, rectum, pancreas, urinary bladder, or the central nervous system (4).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of surgical excision still remains controversial. It has been reported that surgical excision has no benefit following chemotherapy and irradiation, except in the presence of progressive neurological deficits such as increasing intracranial pressure or disturbance of consciousness which are uncontrollable by the conservative treatment 11) . Surgical resection and/or irradiation, although highly effective in local control, do not influence survival 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection and/or irradiation, although highly effective in local control, do not influence survival 6) . Moreover, surgery would increase the risk of infection and CNS dissemination 11) . However, some reports noted that surgical decompression might provide rapid improvement and lead to a long symptom-free period 19) .…”
Section: Discussionmentioning
confidence: 99%